Introduction to twenty two new Asian short stories - Quayum, Mohammad Abdul (Silverfish Books, 2016)
This chapter outlines the gowth and development of Asian short stories in the English language in recent years and explains the rationale for publishing this book as well for including the stories featured in the volume. It introduces the stories in the book in considerable detail and explains the future possibilties of Asian short stories in English.